Construction of Students Knowledge of Disasters Based on Curriculum 13 in Jember District - Arifin, Zainul; Handayani, Baiq Lily (Jurnal ENTITAS SOSIOLOGI, 2019)
This study aims to analyze the construction of students' knowledge of disaster through curriculum 13. This research conducts in two schools, namely SDIT Harapan Ummat Jember and SD Muhammadiyah 01 Jember. Knowledge of the disaster is vital, especially to children who are in the category of vulnerable people. This study used a qualitative descriptive method. Through the theory of social construction (Peter Berger and Thomas Luckman), the researcher analyzes the data. The development of the student's knowledge acquired from books disaster curriculum 13, which is then developed by teachers to increase understanding of the students. The school is also working with the relevant agencies such as regional disaster management agencies, the University of Jember, and Muhammadiyah Disaster Management Center to provide more in-depth knowledge to their students. In the process, the students acquire knowledge Externalization of the disaster through the materials on curriculum 13 on environment and disaster. Later in the process of objectivation, student's understanding of the catastrophe was strengthened with new learning media provided by the teacher by showing videos and photos on disaster occurrence. Keywords: knowledge's construction, elementary students, disasters, Curriculum 13 Referensi: Berger, L. P. dan Luckman, T. 1990. Tafsir Sosial Atas Kenyataan. Jakarta: LP3ES. BNPB. 2010. Peraturan Kepala Badan Nasional Penanggulangan Bencana No.24 Tahun 2010. Tentang Pedoman Penyusunan Rencana Operasi Darurat Bencana. Jakarta Bungin, B. 2008. Konstruksi Sosial Media Massa. Jakarta: Kencana Prenada Media Group. Maarif, Syamsul. 2007. Pengenaln Karakteristik Bencana dan Upaya Mitigasinya di Indonesia. Edisi II. Jakarta: Bakornas PB. Gugus Tugas Pengarusutamaan Pengurangan Risiko Bencana dalam Sistem Pendidikan Nasional. 2010. Strategi Pengarusutamaan Pengurangan Risiko Bencana di Sekolah. Jakarta : KEMENDIKNAS Kunandar. (2013). Penilaian Hasil Belajar Peserta Didik Berdasarkan Kurikulum 2013. Jakarta: Raja Grafindo Persada. Ramli, Soehatman. 2010, Manajemen Bencana, Jakarta: Dian Rakyat Maarif, Syamsul. 2012. Pikiran dan Gagasan Penanggulangan Bencana di Indonesia. Jakarta: BNPB Moleong. J Lexy. 2007. Metode Penelitian Kualitatif. Edisi revisi. Bandung: PT Remaja Rosdakarya. Nurhayati, Anindita, dan Purwawangsa. 2012. Persepsi Masyarakat Terhadap Sistem Peringatan Dini (Early Warning System) Sebagai Upaya Pencegahan Kebakaran Hutan Perum Perhutani KPH Pasuruan, Jawa Timur. Jurnal Silvikultur Tropika Vol.03 No.03 (149- 154)ISSN 2056 8227 Nurjanah, dkk. 2011. Manajemen Bencana. Jakarta: Alfabeta Parera, F.M. 2013. Tafsir Sosial Atas Kenyataan. Jakarta : LP3ES Peraturan Kepala Badan Nasional Penanggulangan Bencana Nomor 02 Tahun 2012 tentang Pedoman Umum Pengkajian Risiko Bencana. Permendikbud (2016). Peraturan Menteri Pendidikan dan Kebudayaan Nomor 24 Tahun 2016 Tentang Kompetensi Inti Dan Kompetensi Dasar Pelaajaran Pada Kurikulum 2013 Pada Pendidikan Dasar Dan Pendidikan Menengah Santrock, John W. 2007. Perkembangan Anak, edisi ketujuh, jilid dua. Jakarta Erlangga. Undang-Undang Republik Indonesia Nomor 24 Tahun 2007 tentang Penanggulangan Bencana. Undang-Undang Republik Indonesia Nomor 39 Tahun 1999 tentang hak asasi manusia.